(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article considers the problem of lexical representation of the concept «anguish» from the perspective of semantic-cognitive approach. The novelty of the research is to describe the cognitive model of the lexical-semantic field of the concept «anguish» through plant characteristics, which reflects the studied concept in language consciousness of native speakers. In order to gain the access to the content of the concept as a thought-unit, the semantic scope of the concept is presented as follows: direct nominations of the concept (a keyword representing the concept which is chosen by the researcher as the name of the concept, the name of the nominative field, and its system synonyms); derivative nominations of the concept; contextual synonyms; occasional individual author nominations; metaphorical nominations; stable comparisons with the keyword; figurative conceptual features that characterize the concept, literary texts that reveal the content of the concept which suggest that the plant characteristics represented by lexical synonyms most accurately reflect the emotions and structured linguistic consciousness.